Study on the Impact of Environmental Governance Effectiveness on Public Participation in Pro-Environmental Behaviour: – An Empirical Analysis from CGSS2021 Data - Jin, Ziqiao (Transactions on Economics, Business and Management Research, 2024)
In recent years, the disharmonious relationship between human beings and the natural environment has become increasingly evident,and ecological and environmental problems have become progressively more serious.Public participation in pro-environmental behaviour is an important measure for the effective protection of the ecological environment and the real realisation of harmonious coexistence between man and nature.However, few current studies on pro-environmental behaviours have analysed pro-environmental behaviours from the perspective of the effects of environmental governance.Therefore,based on the theory of "attitude-behaviour-situation", this study constructed an ordered probability unit model to investigate the impact of environmental governance on public participation in pro-environmental behaviours.The empirical test was conducted by using data from a sample of 7617 households from the 2021 China General Social Survey using stata 17.0 software. The results show that environmental governance effects significantly influence citizens’ private domain pro-environmental behaviour, while the effects are insignificant in terms of public domain pro-environmental behaviour. Meanwhile, through the heterogeneity test, it was found that age and socio-economic status positively motivate public participation in private pro-environmental behaviours, while the number of family members negatively motivates public participation in private pro-environmental behaviours.The results of this paper have some implications for environmental governance.